СТРАТЕГИЯ КНР В ДЕЯТЕЛЬНОСТИ И РАЗВИТИИ ВОЗ - Хуан Куньпэн (International Journal of Innovative Technologies in Social Science, 2020)
At present, the influence of globalization is especially noticeable in the economic, political, religious and cultural fields. However, the lack of boundaries in diseases and the value of health for all nations are determined by the fact that the development of global health management will not be limited by anti-globalization tendencies and campaigns. Global health management is one of the most important issues in the context of global governance, both now and in the future. WHO, as the world’s largest official health organization, is of particular importance. For China as a developing country, strengthening its representation in the World Health Organization, as well as integration into the global health management system, are seen as leading strategic objectives in the framework of China’s participation in global governance. Relevant events of the World Health Organization define the strategy for health diplomacy in China.